Time-varying sliding-coefficient-based decoupled terminal sliding-mode control for a class of fourth-order systems - Bayramoğlu, Hüsnü; Kömürcügil, Hasan (ELSEVIER SCIENCE INC, 2014)
A time-varying sliding-coefficient-based decoupled terminal sliding mode control strategy is presented for a class of fourth-order systems. First, the fourth-order system is decoupled into two second-order subsystems. The sliding surface of each subsystem was designed by utilizing time-varying coefficients. Then, the control target of one subsystem to another subsystem was embedded. Thereafter, a terminal sliding mode control method was utilized to make both subsystems converge to their equilibrium points in finite time. The simulation results on the inverted pendulum system demonstrate that the proposed method exhibits a considerable improvement in terms of a faster dynamic response and lower IAE and ITAE values as compared with the existing decoupled control methods. (c) 2014 ISA. Published by Elsevier Ltd. All rights reserved.
The file in this item is the post-print version of the article (author’s copy; author’s final manuscript, accepted for publication after peer-review process). Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: INSTRUMENTS & INSTRUMENTATION, DESIGN, Finite time convergence; ENGINEERING, MULTIDISCIPLINARY, Decoupled sliding-mode control, AUTOMATION & CONTROL SYSTEMS; Terminal sliding-mode control, NONLINEAR-SYSTEMS, Sliding-mode control, INPUT FUZZY-LOGIC